Occurrence of Parasitic Tapeworm Bothridium pithonis (Class: Cestoda) in Puff-Faced Water Snake (Homalopsis buccata) - Ryanka Edila; Aditya Yudhana; Ratih Novita Praja; April Hari Wardhana; Kwon Hyuck Keun; Amin Nur Asdiyanta; Frenky Laksana Putra; Januar Firmansyah; Marcella Jessica Hartomoro; Muhammad Rizal Maulana (The Indian Veterinary Journal, 2023)
The puff-faced water snake (Homalopsis buccata) is an aquatic snake which have wide distribution in tropical areas predominately Indonesia. A dead puff-faced water snake due to electrical by catch was collected from the local Sempu River, Banyuwangi District, East Java Province, Indonesia. The number of tapeworm collected and identified using semichen-acetic carmine staining. The results of this study found that puff-faced water snake was infected with parasitic tapeworm in intestinal tissues, namely Bothridium pithonis. The Bothridium pithonis finding may contribute for further understanding and parasite study, considering only few global reports in Bothridium pithonis infection occurrence, predominately in wild snakes.